The Effect of Classical Music Therapy and Expressive Writing Combination on Anxiety Scores of Primigravid Pregnant Women in the Third Trimester at Cibeureum Public Health Center in Tasikmalaya City - Selvia Dewi, Selvia Dewi; Peni Cahyati, Peni Cahyati; Ridwan Kustiawa, Ridwan Kustiawan; Dudi Hartono, Dudi Hartono (Jurnal Medika Cendikia, 2025)
Primigravida pregnant women in the third trimester are prone to anxiety triggered by uncertainty before giving birth and adapting to the new role as parents. Excessive anxiety risks causing negative impacts on maternal and fetal health, such as sleep disorders, preeclampsia, premature birth, and low birth weight. Therefore, effective non-pharmacological interventions are needed to help reduce anxiety levels in pregnant women. This study aims to determine the effect of a combination of classical music therapy and expressive writing on anxiety scores of primigravida pregnant women in the third trimester at the Cibeureum Health Center, Tasikmalaya City. This study used a quantitative approach with a pre-experimental design and a one group pretest-posttest approach. The research sample consisted of 26 respondents selected by purposive sampling. The intervention in the form of classical music therapy and expressive writing was given for three consecutive days with a duration of 20–30 minutes per session. Anxiety scores were measured using the Hamilton Anxiety Rating Scale (HARS) before and after the intervention. Data analysis used the paired sample t-test statistical test. The results showed a significant decrease in anxiety scores after being given a combination of classical music therapy and expressive writing. The p value obtained was 0.000 (p <0.05), which indicated that the difference before and after the intervention was statistically significant. The combination of classical music therapy and expressive writing has been proven effective in reducing anxiety scores in primigravida pregnant women in the third trimester. This intervention is recommended as a non-pharmacological alternative that can be applied in primary health services to support the mental health of pregnant women.